The Utilization of U-Dictionary to Improve Students’ Pronunciation - Maulida, Nabiela; Sakhiyya, Zulfa; Rukmini, Dwi (English Education Journal, 2023)
The main aim of this research is to assess the effectiveness of U-Dictionary in enhancing the pronunciation skills of students. The ability to pronounce words correctly is a crucial aspect of foreign language acquisition, particularly for Indonesian learners, and it plays a vital role in effective communication. Many English language learners face difficulties in pronouncing words when they speak, read, or listen to English. In today's digital age, mobile applications offer a variety of learning opportunities, including online learning through smartphones.This qualitative study delves into the use of U-Dictionary to augment students' pronunciation skills, and the author provides a detailed account of the research findings. The researchers observed a group of second-grade students at MTs Maarif Andong who were selected for this study. Thirty students participated as respondents and were interviewed and given questionnaires to provide accurate information. The findings indicate that the majority of students found media to be helpful in improving their pronunciation and believed that learning pronunciation is crucial. They also perceived the "perfect English pronunciation feature" in U-Dictionary as a practical and enjoyable way to overcome difficulties in learning pronunciation.